A Bibliometric Analysis Of Geotextile As Underground Filtration In Subsurface Drainage Towards Slope Stability Using Vosviewer - Jason Budiono; Andri Irfan Rifai; Ade Jaya Saputra; Susanty Handayani (Riviera Publishing, 2024)
Geotextile is a geosynthetics tool in civil engineering that addresses geotechnical issues. As an alternative employed in dealing with the soil foundation, geotextiles serve functions such as separation, filtration, drainage, reinforcement, stabilization, protection, and a combination of these functions. This study aimed to systematically map the scientific research outcomes on slope stabilization and geotextiles using a quantitative review method known as bibliometric analysis. Bibliometric analysis is a widely used and robust method for investigating and analyzing extensive scientific data sets. This approach allows us to unravel the evolutionary intricacies within a particular field and illuminate emerging areas. With the help of Publish or Perish, the data sourced from the Crossref database will be analyzed using VOSviewer software. The results indicated that the most document publications occurred in 2023, with 74 journals published that year. The findings revealed a significant focus on slope reinforcement among researchers, as evident in the 810 articles published from 2000 to 2023. Of these, 54% consisted of papers published in journal articles. In summary, this research provides a quantitative examination of trends and future directions in this research field, serving as a valuable resource for researchers. Also, this paper will serve as a valuable reference for acquiring insights into the available techniques and procedures for conducting studies utilizing bibliometric analysis.